Macroporous resin purification and quantification by LC-MS of bioactive flavonoids in Ginkgo biloba leaves - Kang Min; Wang Xiaojing (CyTA - Journal of Food)
Ginkgo biloba leaves (GBL), a traditional Chinese medicinal resource, are recognised for their rich flavonoid content with diverse bioactivities. This study optimised the purification of total flavonoids from GBL using macroporous adsorption resin and quantified the compounds via LC-MS. Among six tested resins, AB-8 exhibited superior performance, with an adsorption capacity of 92.54 ± 0.85 mg/g and a desorption capacity of 71.03 ± 1.83 mg/g. The adsorption process followed the Langmuir isotherm and pseudo-first-order kinetics, indicating favourable, spontaneous, and exothermic physical adsorption. Scale-up column chromatography under optimised conditions (adsorption: 6 BV of GBLF extract at 1.5 BV/h; desorption: 5.5 BV of 60% ethanol at 3 BV/h) increased flavonoid purity by 5-fold (from 7.08% to 36.20 ± 0.45%) with a recovery rate of 36.20 ± 0.45%. LC-MS analysis identified 17 major flavonoids, 14 of which showed significant enrichment after purification. These findings establish a robust framework for industrial-scale flavonoid purification from GBL.